Skin Imaging Using Ultrasound Imaging, Optical Coherence Tomography, Confocal Microscopy, and Two-Photon Microscopy in Cutaneous Oncology - Oh, Byung Ho; Kim, Ki Hean; Chung, Kee Yang (Frontiers in Medicine, 2019)
With the recognition of dermoscopy as a new medical technology and its available fee assessment in Korea comes an increased interest in imaging-based dermatological diagnosis. For the dermatologist, who treats benign tumors and malignant skin cancers, imaging-based evaluations can assist with determining the surgical method and future follow-up plans. The identification of the tumor’s location and the existence of blood vessels can guide safe treatment and enable the use of minimal incisions. The recent development of high-resolution microscopy based on laser reflection has enabled observation of the skin at the cellular level. Despite the limitation of a shallow imaging depth, non-invasive light–based histopathologic examinations are being investigated as a rapid and pain-free process that would be appreciated by patients and feature reduced time from consultation to treatment. In the United States, the current procedural terminology billing code was established for reflectance confocal microscopy in 2016 and has been used for the skin cancer diagnosis ever since. In this review, we introduce the basic concepts and images of ultrasound imaging, optical coherence tomography, confocal microscopy, and two-photon microscopy and discuss how they can be utilized in the field of dermatological oncology.